2013
DOI: 10.1111/bij.12170
|View full text |Cite
|
Sign up to set email alerts
|

Hidden diversity ofEuscorpius(Scorpiones: Euscorpiidae) in Greece revealed by multilocus species-delimitation approaches

Abstract: Phylogenetic analysis of the genus Euscorpius (Scorpiones: Euscorpiidae) across the Mediterranean region (86 specimens, 77 localities, four DNA markers: 16S rDNA, COI, COII, and ITS1), focusing on Greek fauna, revealed high variation, deep clade divergences, many cryptic lineages, paraphyly at subgenus level, and sympatry of several new and formerly known lineages. Numerous specimens from mainland and insular Greece, undoubtedly the least studied region of the genus' distribution, have been included. The recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 57 publications
10
80
0
Order By: Relevance
“…Consistent with previous studies (e.g. Dennis et al, 2000;Fattorini, 2002;Hausdorf & Hennig, 2005;Simaiakis & Mart ınez-Morales, 2010;Strona et al, 2012;Parmakelis et al, 2013) our results highlighted the role of palaeogeographical events and geographical configuration on biodiversity and species assemblage patterns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies (e.g. Dennis et al, 2000;Fattorini, 2002;Hausdorf & Hennig, 2005;Simaiakis & Mart ınez-Morales, 2010;Strona et al, 2012;Parmakelis et al, 2013) our results highlighted the role of palaeogeographical events and geographical configuration on biodiversity and species assemblage patterns.…”
Section: Discussionsupporting
confidence: 92%
“…In Europe, one of the most thoroughly investigated regions of the world in terms of biodiversity (Fontaine et al, 2012), this problem is not as great as in other continents, although some groups have received more attention than others (e.g. Dennis et al, 2000;Allegrucci et al, 2009;Papadopoulou et al, 2009;C ßiplak et al, 2010;Fattorini & Baselga, 2012;Fiera & Ulrich, 2012;Parmakelis et al, 2013;Ulrich & Fattorini, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed phylogeographic studies of wide‐ranging scorpion species continue to discover that scorpions found across large areas and diverse habitat types often represent cryptic complexes of more stenotypic species (Bryson et al, , ; Habel et al, ; Parmakelis et al, ; Sousa et al, ). Such is the case for the Mesobuthus caucasicus complex (Fet et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction, PCR amplifications and sequencing was performed as described in Parmakelis et al (2013). Sequence editing and alignment was performed using Codon Code Aligner v.2.06.…”
Section: Sequence Data Generation and Phylogenetic Analysesmentioning
confidence: 99%
“…The remaining five species, E. avcii, E. koci, E. gocmeni, E. lycius and E. rahsenae, are similar to the forms of the subgenus Euscorpius, with the trichobothrial number on the pedipalp manus ventral surface 4 (V 1-3 + Et 1 ) and the trichobothrial series on the pedipalp patella external surface em = 4. However, the diagnostic characters of the subgenus Euscorpius are currently obsolete, as this traditional subgenus appears to be paraphyletic (Parmakelis et al, 2013;. Therefore, the five above mentioned Turkish species, as well as E. alanyaensis sp.…”
Section: Comparisonsmentioning
confidence: 99%